Monomorphic epitheliotropic intestinal T-cell lymphomas: a case report - Haibin Zhong; Yang Zheng; Feiran Zhang (BMC, 2021)
Abstract Background Monomorphic epitheliotropic intestinal T-cell lymphomas (MEITL) is a rare and aggressive subtype of lymphoma. The most common site of origin is small intestine. Patients are often presented with diagnosis of intestinal perforation with abdominal pain as the main consulting symptoms. Because of the deficiency of specific diagnostic measures and effective management, diagnosis is often confirmed in advanced stage with poor prognosis. Case presentation Here, we introduce a patient who has suffered from abdominal pain and diarrhea, and eventually been diagnosed as Monomorphic epitheliotropic intestinal T-cell lymphomas. Conclusion MEITL is rare in clinical practice with deficiency of early diagnostic measures and poor prognosis. Therefore, any patient with ambiguous gastrointestinal symptoms or perforation of the digestive tract where the primary lesion is difficult to identify should be alert to the possibility of this disease.